(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Palusita, a new genus of the tribe Euliini and its two species (P. paulista Razowski & Becker, P. ochrans Razowski & Becker) are described from Eastern and Centrai Brazil.